Suatu fq-Derivasi pada BE-Aljabar - Jayanti, Endah Dwi (JOSTECH Journal of Science and Technology, 2024)
In this article, the concept of f_q-derivation in BE-algebra is given by first defining a mapping φ_q^f, which is a self-map of BE-algebra. Based on this definition, the concept of f_q-derivation in BE-algebra is constructed. The results of this research are the definition of f_q-derivation in BE-algebra and its properties. These properties are constructed from the mapping φ_q^f, regular, fixed set, and kernel of a f_q-derivation in BE-algebra.